1993
DOI: 10.1002/ejsp.2420230604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intergroup similarity on intergroup relations

Abstract: We examined the impact of intergroup similarity on two aspects of intergroup relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 27 publications
6
104
0
3
Order By: Relevance
“…If one does not regard a particular identity as central to their self-defi nition, they are unlikely to use it as a source of self-esteem (Branscombe, Wann, Noel, & Coleman, 1993). Work carried out by Manstead (1996, 2001; see also Roccas & Schwartz, 1993) has examined the reactions of individuals that attach little, or much, importance to social categories under conditions of threatened group distinctiveness. Using similarity of group norms as the distinctiveness manipulation, it was found that intergroup similarity (i.e.…”
Section: Identifi Cation and Subgroup Distinctivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…If one does not regard a particular identity as central to their self-defi nition, they are unlikely to use it as a source of self-esteem (Branscombe, Wann, Noel, & Coleman, 1993). Work carried out by Manstead (1996, 2001; see also Roccas & Schwartz, 1993) has examined the reactions of individuals that attach little, or much, importance to social categories under conditions of threatened group distinctiveness. Using similarity of group norms as the distinctiveness manipulation, it was found that intergroup similarity (i.e.…”
Section: Identifi Cation and Subgroup Distinctivenessmentioning
confidence: 99%
“…Spears et al, 1997). Thus, perceived threat to the continuation of the initial ingroup identity via recategorization would lead to, at best, no effect on bias, or, at worst, an increase in intergroup bias (Crisp & Beck, 2005;Crisp et al, 2006;Hornsey & Hogg, 2000a;Roccas & Schwartz, 1993;van Leeuwen et al, 2003). One could argue that recategorization contexts represent little more than alternative means of manipulating intergroup similarity, something that has been examined in the social identity literature with respect to subgroup identifi cation for some time.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Such a sense of self is reflected in agents' behaviour. As Mitzen argues, 'ontological security is security not of the body but of the self, the subjective sense of who one is, which enables and motivates action 4 There is also a trend within the social identity perspective (Tajfel 1978;Tajfel and Turner 1986) arguing that differentiation increases when group distinctiveness is low and threatened by similarity with other groups (Moghaddam and Stringer 1988;Roccas and Schwartz 1993;e.g. Dovidio, Gaertner, and Validzic 1998;Jetten, Spears, and Manstead 2001 and choice ' (2006:344).…”
Section: Ontological (In)security: a Theoretical Frameworkmentioning
confidence: 99%
“…Previous literature has emphasized similarity--the uniqueness literature argues divergence is driven by similar others and some social identity research has argued groups feel increased pressure to differentiate themselves from similar outgroups (Brown & Abrams, 1986;Diehl, 1988;Jetten, Spears, & Manstead, 1997;Roccas & Schwartz, 1993). Previous research has not explained, however, why groups might want to differentiate themselves from dissimilar others.…”
Section: Summary: Who Drives Divergence and Why?mentioning
confidence: 99%